Innovation and Resilience: SMEs Facing the Crisis Caused by Covid-19. A Narrative Review of the Literature - Martelo-Castro, Mayerlin (2023)
To stop the pandemic caused by Covid-19, both individuals and companies were forced to pause most of their daily activities, causing a crisis in trade and the global economy. In particular, SMEs suffered a great impact, partly due to their economic vulnerability and survival economy. However, for some, the small size and flexible structure were drivers of change and adaptation. The purpose of this article is to provide a narrative about adaptation in SMEs in the face of the Covid-19 pandemic, exploring processes and strategies used to guarantee their survival. From the methodological point of view, a narrative review of the scientific production literature was carried out in the WOS and Scopus databases, and the documentary analysis base was built as a semi-systematic review of the literature. The main findings identified two adaptation processes in SMEs to face the pandemic: innovation and resilience, mediated by strategies such as the use of technologies and external collaborations, in understanding the new needs of customers. This review seeks to increase the theoretical framework for future research and that the proposed strategies serve as possible guides for companies in future eventualities.